THU0482 HUMAN LUMBAR SPINE FACET JOINT OSTEOARTHRITIS DISPLAYS PREDOMINANT NGF EXPRESSION AND SIGNALING IN CAPSULAR SYNOVIUM AND SUBCHONDRAL BONE MARROW TISSUES INDEPENDENT OF OSTEOARTHRITIS GRADE. (June 2019) - Seidel, Matthias; Busso, Nathalie; Chobaz, Veronique; Netzer, Cordula; Huegle, Thomas; Geurts, Jeroen
Abstract : Background: Increased nerve growth factor (NGF) levels are associated with chronic pain conditions, including low back pain and osteoarthritis (OA). NGF signalling through its receptor TrkA regulates pro-inflammatory neurotransmitters such as substance P (SP). Inhibition of NGF has shown therapeutic efficacy in knee OA [1] and chronic back pain [2], but trials have revealed rare cases of rapidly progressive OA of peripheral joints. Objectives: To describe the tissue distribution of NGF, TrkA, SP and macrophages in facet joint osteoarthritis (FJOA) of the lumbar spine and their association with FJOA grade. Methods: FJOA specimens were obtained by facetectomy from patients undergoing intervertebral fusion (n =10, average age 69 years, 5 males). FJOA severity and presence of synovial hypertrophy was graded using preoperative magnetic resonance imaging (MRI). Relative abundance of NGF, CD68 (macrophages), TrkA and SP in capsular synovium (SY), cartilage (CL), subchondral bone (SB) and subchondral bone marrow (BM) was evaluated semi-quantitatively on a scale ranging from 0-3 using immunohistochemistry. Association between imaging parameters and tissue expression was determined using Pearson correlation analysis. Results: Synovial hypertrophy as determined by MRI was present in six cases (60%) and median Weishaupt grade of FJOA was 2 (1.5-3) corresponding with moderate to severe OA. NGF was abundantly expressed in SY (3 [0.5-3]) and to a lesser extent in BM tissues (2 [1-3]), whereas TrkA expression was detected in BM exclusively. NGF abundance in SY and BM showed a strong correlation ( r = 0.94), but did not associate with synovial hypertrophy or FJOA severity. CD68+ macrophages were highly abundant in BM (3 [1.5-3]) and sparse in SY tissues (0.5 [0-1]). The relative abundance of macrophages and NGF was strongly correlated in SY tissue only ( r = 0.78). SP as a downstream mediator of NGF signalling was also abundantly expressed in SY, CL and BM tissues. Tissue distributions of CD68, NGF and SP are summarized in the figure. Conclusion: NGF expression and signalling is evident in lumbar spine FJOA specimens, but not strongly associated with synovial hypertrophy or disease severity. These results are in agreement with recent studies of human knee OA, which have shown osteochondral NGF expression as a hallmark of symptomatic OA independently of chondropathy or synovitis [3]. References: [1] Lane NE, Schnitzer TJ, Birbara CA, Mokhtarani M, Shelton DL, Smith MD, Brown MT.(2010) Tanezumab for the treatment of pain from osteoarthritis of the knee. N Engl J Med. 363:1521. [2] Katz N, Borenstein DG, Birbara CA, Bramson C, Nemeth MA, Smith MD, Brown MT. (2011) Efficacy and safety of tanezumab in the treatment of chronic low back pain. Pain. 152(10):2248 [3] Aso K, Shahtaheri SM, Hill R, Wilson D, McWilliams DF, Walsh DA. (2019) Associations of symptomatic knee OA with histopathologic features in subchondral bone. Arthritis Rheumatol. ePub Disclosure of Interests: Matthias Seidel Grant/research support from: Pfizer, Actelion, Consultant for: Pfizer, Lilly, Nathalie Busso: None declared, Veronique Chobaz: None declared, Cordula Netzer: None declared, Thomas Huegle Grant/research support from: AbbVie, Lilly, Novartis and Pfizer, Speakers bureau: AbbVie, Lilly, Novartis and Pfizer, Jeroen Geurts: None declared